Implementation of Islamic Character Based Education In Students’ Religious Extracurricular Activities - Trinova, Zulvia; Rehani; Yuniendel , Ratna Kasni; Riswandi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Problems found in the field are lack of student time discipline, untidy clothing, ignorance of prayers, inappropriate use of speech, lack of proper lip service. This study aims to describe the types of Islamic character-based education programs in religious extracurricular activities, explain these activities carried out, and describe the results of Islamic character-based education for students participating in this activity. Descriptive method is used with a qualitative approach. Data informants are advisors on religious extracurricular activities, principals, deputy heads of student affairs, trainers and students. Data were collected through observation, and interviews, and analyzed through descriptive analysis techniques, and validity testing with data triangulation techniques. The research findings are: type of Islamic character-based education program in extracurricular religious activities is part of a religious activity program, the methods and materials used contain Islamic characters, Islamic character-based education is carried out outside hours of curricular activities with a specified time each week, with material developed from Islamic Religion, developed with relevant methods and supported by existing facilities; and religious activities are able to educate the Islamic character of students. The Islamic character is seen from the religious activities of Rohis, Hadrah and Nasyid